Belly and body in the Pauline Epistles - Sandnes, Karl Olav, 1954- (Monograph series (Society for New Testament Studies), 2002)
The belly is today a matter of much concern. Modern cultures have developed means to cultivate this part of the body. Does St Paul in any way address a culture in which the stomach is similarly high on the agenda? To answer this question is the aim of this investigation.